Pelatihan Pembuatan Pupuk Organik Cair Eco Enzym bersama BUMDES Desa Jembulwunut - Abdul Manaf; Irfai Fathurohman (Universitas Muria Kudus, 2024)
From the observation activities of the Field Study and Community Service (Kuliah Kerja Nyata) 112 team in Jembulwunut village, they obtained data that the majority of people work as farmers, however they find it difficult to obtain fertilizer, practicing how to make Eco-enzyme organic fertilizer with Village-Owned Enterprise (Badan Usaha Milik Desa) Jembulwunut to support agricultural development, particularly reducing environmental pollution of agricultural land because of the materials used are organic waste such as vegetable and fruit waste that cannot be consumed anymore, it has high nutrient elements to maintain soil fertility and as a substitute for synthetic chemical fertilizers which are difficult to obtain and whose prices are getting higher every year.